2017
DOI: 10.7717/peerj.3041
|View full text |Cite
|
Sign up to set email alerts
|

Tartrazine induces structural and functional aberrations and genotoxic effectsin vivo

Abstract: Tartrazine is a synthetic organic azo dye widely used in food and pharmaceutical products. The current study aimed to evaluate the possible adverse effect of this coloring food additive on renal and hepatic structures and functions. Also, the genotoxic potential of tartrazine on white blood cells was investigated using comet assay. Twenty adult male Wistar rats were grouped into two groups of 10 each, control- and tartrazine-treated groups. The control group was administered orally with water alone. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 30 publications
14
62
0
2
Order By: Relevance
“…Interestingly, the levels of MDA significantly increased in rats treated with Sunset Yellow or Allura Red, indicating an increased oxidative stress due to over-production of reactive oxygen species. Our findings concur with Sarhan, Shati and Elsaid (2014) and Khayyat et al (2017), who reported an elevation of serum MDA after treatment of rats with food chemical colourants. Moreover, Gil (2014) demonstrated that Sunset Yellow induces the oxidative stress response in H295R cells in vitro.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the levels of MDA significantly increased in rats treated with Sunset Yellow or Allura Red, indicating an increased oxidative stress due to over-production of reactive oxygen species. Our findings concur with Sarhan, Shati and Elsaid (2014) and Khayyat et al (2017), who reported an elevation of serum MDA after treatment of rats with food chemical colourants. Moreover, Gil (2014) demonstrated that Sunset Yellow induces the oxidative stress response in H295R cells in vitro.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 93%
“…Hameid & Abd Elsttar, 2010). Similar observations were previously reported in rats treated with Sunset Yellow (Tawfek et al, 2015;Abd Elhalem et al, 2016), tartrazine (Khayyat et al, 2017) and Fast Green (Ashour & Abdelaziz, 2017). The same parameters can be used to classify a food colourant as a harmful agent, depending on its metabolic activation to form free radicals.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 87%
“…It is water soluble mono azo color which used in human food, pharmaceutical products and cosmetics. Many countries are using Tz as saffron substitute (Himri et al, 2011;Ali et al, 2016;Khayyat et al, 2017).The JECFA evaluated ADI to be 0-7.5 mg/kg/day (Moutinho et al, 2007;Himri et al, 2011;Ali et al, 2016). The metabolites generate ROS which cause oxidative stress (EFSA, 2009;Himri et al, 2011;Khayyat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many countries are using Tz as saffron substitute (Himri et al, 2011;Ali et al, 2016;Khayyat et al, 2017).The JECFA evaluated ADI to be 0-7.5 mg/kg/day (Moutinho et al, 2007;Himri et al, 2011;Ali et al, 2016). The metabolites generate ROS which cause oxidative stress (EFSA, 2009;Himri et al, 2011;Khayyat et al, 2017). Also, it promoting lipid peroxidation and inhibiting endogenous antioxidant defense enzymes which, in turn, accelerate oxidative stress and damage most cellular components leading finally to cell death (Morales et al, 2004;Boussada et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic colorants tends to be harmful as they can render allergenic and intolerance reactions to human beings 4 . Meanwhile, the colours from natural sources are proved to be safe due to their non-carcinogenic, non-toxic and biodegradable in nature properties 5 .…”
mentioning
confidence: 99%